The Islamic Vocabulary Philanthropy in Enhancing English Language Learning Among Students at As’adiyah Islamic Boarding School Sengkang - Muhammad Lutfi Alwi; Ambo Dalle; Abdul Haris Sunubi; Arqam; Magdahalena Tjalla (Universitas Muhammadiyah Palu, 2024)
This research aims to improve the vocabulary of philanthropy-related terms among 8th-grade students (class 8.1) at Male Islamic Junior High School of As’adiyah Sengkang. Currently, these students have low English proficiency, especially in vocabulary. Data includes qualitative and quantitative aspects. Qualitative data relates to the teaching process, while quantitative data comes from pretests and post-tests analyzed using t-tests. Data sources include the 22 students and their English teacher. Following Mills' theory, data collection includes observations, interviews, questionnaires, and vocabulary tests, recorded in the Researcher’s Daily Notes. This research investigated how using language games can improve English vocabulary for grade 8 students in Male Islamic Junior High School of As’adiyah Sengkang. The games were designed to be fun and interesting for the students and included things like pictures, songs, and practice exercises. The study found that the students' vocabulary knowledge improved a lot after playing the language games.